Pengetahuan Orang Tua Tentang Obesitas Pada Anak - Rika Andriyani; Lucky Shinta Febrianti (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2014)
Background: According to data of survey which is Institute Survey Gizi and Health of National ( NHANES) or of National Health And Nutrition Examination Survey number of obesitas increasing manifestly at child, one of them at age group 6-12 year which is its occurence number mount from 6,5% becoming 17%. Pursuant to field observation in SD Santa Maria Pekanbaru with interview to 10 old fellow owning age child 6-12 year, got by conclusion 7 among 10 old fellow do not know factor influencing child become obesitas one of them is the lack of knowledge of old fellow to obesitas, clan factor, economic factor, often consume food of junk food, and also the lack of physical activity.Objective: Target of this research to know picture knowledge of old fellow about obesitas at child in SD Santa Maria Pekanbaru year 2014.Method: This Research type of descriptive method. Amount of sampel counted 95 people with sampling technique of proporsional and of simple sampling random. Data-Processing manually data analysis and of univariat.Result: From result of this research is concluded that knowledge of old fellow about obesitas in SD Santa Maria Pekanbaru from 95 accurate by responder of majority 48 people (50,52%) knowledgeable less and minority 47 people (49,47%) is knowledgeable of goodness.Keyword: Knowledge, Obesitas